GAMBARAN STATUS KEBERSIHAN RONGGA MULUT DAN KESEHATAN JARINGAN PERIODONTAL PADA LANSIA DI WILAYAH PERKEBUNAN RENTENG (STUDI KASUS DI DESA MANGARAN, KECAMATAN AJUNG, KABUPATEN JEMBER) - Sonya Cut Yumita Putri,; Peni Pujiastuti,; Depi Praharani, (Jurnal Kesehatan, 2025)
Periodontal disease is an infection in the tissues supporting the teeth. In general, periodontal disease consists of gingivitis and periodontitis. The main cause of this disease is dental plaque bacteria. This disease can affect anyone, including the elderly. Periodontal disease is caused by degenerative changes and plaque accumulation over a long period of time. The purpose of this study was to determine the description of oral hygiene status and periodontal health of elderly in Renteng Plantation area (Mangaran Village, Ajung District, Jember Regency). The research method was observational descriptive cross-sectional, with 90 people divided into two groups of 60–69 years and 70 years. The examinations included oral hygiene with OHI-S and periodontal tissue health with CPITN are presented in tables and figures. The results showed that the level of oral hygiene based on the OHI-S score was 1 person (1.1%) classified as good, 14 people (15.6%) classified as moderate, and 75 people (83.3%) classified as poor. In examining the health status of periodontal tissue based on the CPITN score, 46 people (51.1%) had score of 2, 40 people (44.4%) had score of 3, and 4 people (4.5%) had score of 4. No one had CPITN scores of 0 and 1. The conclusion is that the oral hygiene status of the elderly in the joint plantation area mostly classified as poor at 83.3%. Meanwhile, the health status of the periodontal tissue was mostly found to have supragingival or subgingival calculus at 51.1%.